Velvet Heart: Systemic Fungal Infection Accompanying With Cardiac Involvement and Review Of The Literature - Demirçin, Sema; Dirol, Fatih; Karagöz, Yaşar Mustafa; Aksoy, Aylin; Kırbaş, Derya Bulgur; Göral, Pelin (The Bulletin of Legal Medicine, 2017)
Injuries and intoxications are frequent cause of deaths in illicit drug users. Drug abuse is also associated with increase in infectious diseases and decreased level of immunity. Especially collective usage of syringes can be remarkably dangerous. It is difficult to diagnose the fungal infections in people whose immune systems are deficient and spreading of the pathogenic microorganisms through the bloodstream can lead to systemic infections which can cause rapid death.In this article, a case of a 45-year-old man is being presented who died due to illicit drug intoxication. Apparent cardiac involvement with systemic fungal infection has been determined at the autopsy. The case has been evaluated with the literature. The skin and cardiac findings of the case are both rare and educational. Besides, this report aims to draw attention to systemic infectious diseases that can be found at autopsies of persons who had used illicit drugs and it is intended to review the measures for the protection of the autopsy personnel.
Keywords: heart; drug use; fungal infection; autopsy; infection prevention; protection